"Zarah-Kubo" Tradition on Eidul Fitri Day in Koto Jayo Village, Tanah Tumbuh, Bungo Regency, Jambi Province (Study: Processes, Cultural Education, Development And Meaning) - Prihan Pangemba; Indrayuda Indrayuda (International Journal of Educational Dynamics, 2021)
This study aims to describe and analyze and examine the Zarah-Kubo procession, the development of Zarah-Kubo and the meaning of Zarah-Kubo on Eid al-Fitr in Koto Jayo Tanah Tumbuh Village, Bungo Regency, Jambi Province. This study uses a qualitative method. Informants in this study were the people of Bungo Regency Generally and Koto Jayo Tanah Tumbuh Village. The instruments in this study were the researchers themselves and assisted with supporting instruments in the form of stationery and cameras. Data collection techniques were carried out using literature study, observation, interviews, and documentation. To ensure the validity of the data, the data was checked using extended participation techniques, observer persistence, and triangulation. The steps to analyze the data are data reduction, data presentation, and conclusion. The results of this study are 1) the development of the Zarah-Kubo Tradition is the result of the thoughts, contents of the heart and what is believed by the executors of the Zarah-Kubo Tradition who are played to read the prayer readings of the Zarah-Kubo tradition where the prayer comes from holy verses Al-Qur'an; 2) the procession of the Zarah-Kubo Tradition in Koto Jayo Tanah Tumbuh Village has a sequence of processions starting from the beginning or preparing for the event starting from the annual meeting of the Koto Jayo village community led by the village head, Ninik Mamak and the Community The village to decide which son will lead the prayers during the pilgrimage, choose the gathering place, determine the community for Badua (to eat together) after the Grave Pilgrimage is over; and 3) The Meaning of the Zarah-Kubo Tradition which was carried out in Koto Jayo Tanah Tumbuh Village which has a very strong meaning in the Koto Jayo Village community because the people there really believe that the meaning of the Zarah-Kubo Tradition is not just a spectacle and also not just a tradition the people of the Growing Land, the meaning of the Zarah-Kubo Tradition itself is also a form of community gratitude to Allah SWT for giving him a long life to be able to feel the Eid al-Fitr and give prayers to relatives who have been left behind.